2004
DOI: 10.1023/b:joyo.0000048069.22681.2c
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Attributes and Adaptations Linked to Achievement Motivation Among Latino Adolescents

Abstract: This exploratory study examined whether associations between perceived school experiences and achievement motivation varied by language acculturation and generational status among a sample of immigrant and U.S. born Latino adolescents (n = 129). Ogbu's (1993) notion of primary and secondary cultural differences was adapted to better suit comparisons within this Latino group using the terms cultural attributes and cultural adaptations. Academic competence, school belonging, and parent involvement were positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 28 publications
4
72
1
3
Order By: Relevance
“…Although the results regarding family connection conflict with existing research, the results regarding neighborhoods and schools may be the result of these youth living in neighborhoods and attending schools that are predominately Latino, providing strong connections and ties to these contexts. In addition, some research has identified strong school connections among Latinos (Ibañ nez, Kuperminc, Jurkovic, & Perilla, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although the results regarding family connection conflict with existing research, the results regarding neighborhoods and schools may be the result of these youth living in neighborhoods and attending schools that are predominately Latino, providing strong connections and ties to these contexts. In addition, some research has identified strong school connections among Latinos (Ibañ nez, Kuperminc, Jurkovic, & Perilla, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…All of these items are related to students' perceptions of being “accepted, respected, included and supported by others in the school social environment” (p. 80)(Goodenow, 1993). It has been widely used—mainly in English-speaking countries—and it has been associated with several variables related to academic achievement, such as increased competence and self-efficacy (Ibañez et al, 2004), increased school attendance (Sánchez et al, 2005), and higher grades (Booker, 2007). Several U.S.-based studies have gathered information from Latino/a or Hispanic students using a Spanish version.…”
Section: Introductionmentioning
confidence: 99%
“…Several U.S.-based studies have gathered information from Latino/a or Hispanic students using a Spanish version. However, these studies only report on a few measures of internal reliability (Goodenow, 1993; Robertson et al, 1998; Ibañez et al, 2004; Sánchez et al, 2005; Kuperminc et al, 2008) and do not provide any information about the construct validity or factor structure of the Spanish version.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that higher levels of school connectedness are associated with higher attendance rates (Sanchez et al, 2005), academic self-efficacy (Ibanez et al, 2004) and better grades (Booker, 2007). To determine the extent to which particular reasons for absence reflected broader problems at school and social/emotional wellbeing, a number of measures were used relating to school connectedness and academic self-concept.…”
Section: Does the Reason Matter? 149mentioning
confidence: 99%